Integrated LPV control for underactuated ship linear track keeping and main diesel engine - Yu Liu; Chen Guo; Shichun Yuan (2008 7th World Congress on Intelligent Control and Automation, 2008)
Based on integrated control for underactuated ship linear track keeping and main diesel engine, A new integrated control arithmetic designed by the linear parameter varying (LPV) system control theory and the closed system poles assigned via state feedback is proposed. The ship motion equations of the MMG model is translated into LPV systems with ship speed as the scheduling parameter. The main engine speed control equation of the MMG model is translated into a LPV system through main engine speed and advance coefficient of propeller as the scheduling parameters. By using the closed system poles assigned via state feedback and polytopic gain scheduled design method with linear matrix inequalities technique, the controller of straight line trajectory and the controller of main engine speed of the underactuated ship are designed. Simulation results are presented to validate the effectiveness of integrated LPV control.